Competitiveness in the enterprise economic security system - Silakova, Hanna (My University, 2020)
The paper defines the interdependence of the concepts of "economic security" and "competitiveness". The essence of competitiveness from the point of view of ensuring the economic security of an enterprise is given. The directions of ensuring the competitive advantages of the enterprise in order to identify and maintain the high competitive position of the enterprise in the market have also been determined. В роботі визначено взаємозалежність понять «економічна безпека» та «конкурентоспроможність». Наведено сутність конкурентоспроможності з точки зору забезпечення економічної безпеки підприємства. Також визначено напрямки забезпечення конкурентних переваг підприємства з метою виявлення та збереження високих конкурентних позицій підприємства на ринку.
Keywords: економічна безпека; загроза; конкуренти; конкуренція; конкурентоспроможність; ринок; economic security; danger; competitors; competition; сompetitiveness; market